2011
DOI: 10.2319/040910-201.1
|View full text |Cite
|
Sign up to set email alerts
|

Does the amount of filler content in sealants used to prevent decalcification on smooth enamel surfaces really matter?

Abstract: Objective: To determine how filler content and an acidic environment affect the retention of sealants placed on smooth enamel surfaces. Materials and Methods: A sample of 120 teeth was randomly divided into six subsamples. Three experimental sealants with identical formulas, with the exception of the amount of filler content (18%, 30%, 50%), were applied according to manufacturers' recommendations. Half of the subsamples were exposed to an acid environment (pH of 2.5) for 96 hours. With the use of a toothbrush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
(31 reference statements)
1
13
0
1
Order By: Relevance
“…Laboratory studies indirectly and directly found an erosive resistance to adhesives and fissure sealants. 43,44 Even under prolonged in vitro erosive challenge, resin-based materials remained on the dental substrate, protecting the dentin against erosion. 43 Different types and brands of adhesives might show different behaviors in terms of adhesion and their ability to protect against enamel erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies indirectly and directly found an erosive resistance to adhesives and fissure sealants. 43,44 Even under prolonged in vitro erosive challenge, resin-based materials remained on the dental substrate, protecting the dentin against erosion. 43 Different types and brands of adhesives might show different behaviors in terms of adhesion and their ability to protect against enamel erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of the ETCH group approximates the 90%-97% retention rate reported by Van Bebber et al, 31 who also used a phosphoric acid etch preparation. The small difference in retention rate may be due to the use of a different sealant (ProSeal) and different filler contents.…”
Section: Discussionmentioning
confidence: 94%
“…Van Bebber et al [29] suggested that sealant durability and wear resistance was not increased in the presence of more filler particles. Pennella [22] found that filled sealant (Opal Seal®) remained intact on over half of the tooth surfaces at 90 days, and significant reduction in WSLs was seen in their Opal Seal® group.…”
Section: Discussionmentioning
confidence: 99%
“…Van Bebber et al [29] meinten, dass die Haltbarkeit von Versieglern und ihre Abnutzungsbeständigkeit nicht mit der Menge an Füllerparti-keln zunehme. Pennella [22] verzeichnete mit einem gefüllten Versiegler (Opal Seal®) intakte Versiegelungen nach 90 Tagen an mehr als der Hälfte der untersuchten Zahnoberflächen sowie signifikant weniger WSL in ihrer Opal-Seal-Gruppe.…”
Section: Diskussionunclassified